Ticket to ride [large type] - Gorman, Edward (Thorndike Press large print mystery, 2010)
For small-town Iowa lawyer Sam McCain the year 1965 is not a sweet one. His father is gravely ill. His elitist boss is just coming out of rehab. The brilliant lawyer he hoped to start a relationship with has gone back to her husband. Still McCain tries to enjoy himself during the town's Labor Day weekend party, reuniting with several old friends - until two of them are murdered for what seems to be a motive buried in the past.